2015
DOI: 10.17533/udea.rccp.v28n3a4
|View full text |Cite
|
Sign up to set email alerts
|

Poultry litter of wood shavings and/or sugarcane bagasse: animal performance and bed quality

Abstract: SummaryBackground: litter provides comfort to animals while improving productive performance and carcass quality. Objective: this study evaluated broiler performance, incidence of contact dermatitis, and quality of poultry litter of wood shavings and/or sugarcane bagasse (SB) after five consecutive flocks. Methods: two thousand birds were raised in five consecutive flocks composed of 400 chicks each. The experiment was set in a completely randomized design with five treatments and four repetitions. The treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…A previous study showed higher plasmid conjugation frequencies in E. coli in wood shavings compared with sugarcane bagasse, even in the absence of antibiotics (Saraiva et al 2020). It might be possible that the higher moisture retention of sugarcane bagasse (Teixeira et al 2015) might affect the availability of antibiotic residues in the litter (Benabdeljelil and Ayachi 1996). Moreover, other factors could also affect the dynamics of plasmid conjugation.…”
Section: Resultsmentioning
confidence: 97%
“…A previous study showed higher plasmid conjugation frequencies in E. coli in wood shavings compared with sugarcane bagasse, even in the absence of antibiotics (Saraiva et al 2020). It might be possible that the higher moisture retention of sugarcane bagasse (Teixeira et al 2015) might affect the availability of antibiotic residues in the litter (Benabdeljelil and Ayachi 1996). Moreover, other factors could also affect the dynamics of plasmid conjugation.…”
Section: Resultsmentioning
confidence: 97%
“…SCB has high water absorbing ability due to its residual sugar content. However, SCB cakes easily (55), and this calls for more research to improve its utilization as bedding material for poultry.…”
Section: Sugar Cane Bagassementioning
confidence: 99%
“…A material with superior cushioning properties such as Erianthus may provide an equivalent cushioning property with a smaller amount of bedding material. Bagasse also has a high cushioning property, and it was reported that replacing wood shavings with bagasse at 75% of the weight of the wood shavings improved the bedding quality and the production performance of broilers (Teixeira et al, 2015). In the same way, the partial replacement of sawdust with Erianthus could be an option to simultaneously improve the physical properties of the bedding material and reduce costs.…”
Section: Cushioning Propertymentioning
confidence: 99%